Gonad quality of sea urchin Paracentrotus lividus cultured in an offshore pilot‐scale trial on the south‐east Italian coast. (25th March 2018) - Volpe, M.G.; Fabbrocini, A.; Siano, F.; Coccia, E.; Scordella, G.; Licchelli, C.; De Sio, F.; Paolucci, M.
Abstract: A pilot project aimed at testing roe enhancement strategies based on offshore Paracentrotus lividus cultures was conducted off the south‐east coast of Italy (Apulia Region). Adult sea urchins were reared in sea cages located 700 m offshore at a depth of 12 m for 3 months. The animals were fed once a week on two formulated diets, prepared mixing nutrients with agar 20 g/Kg and differing only in terms of the protein source: anchovy flour (Diet A) or krill flour (Diet K). At the end of the rearing trial, the gonad somatic index of sea urchins fed on formulated diets significantly exceeded that of wild sea urchins. Total FAA content in the gonads of wild sea urchins and Diet A‐fed sea urchins was similar, whereas in Diet K‐fed sea urchins it was significantly higher. In terms of fatty acids, the gonads contained SFAs, MUFAs and PUFAs. In visual and sensory assessment of gonads by panel test and electronic nose, the gonads of reared sea urchins were rated as being of better size, while no differences were recorded for coloration, taste and odour. This study shows that under these experimental conditions, commercial‐grade Paracentrotus lividus roe enhancement can be achieved after 3 months in sea cages.